Moisture-curable siloxane composition
By adding organohydroxypolysiloxane, organopolysiloxane, alkoxy group-containing silane compounds, curing catalysts and tackifiers to the moisture-cured silicone composition, the problem that the moisture-cured organopolysiloxane composition in the prior art is difficult to achieve excellent adhesion to the substrate and transparency of the coating film without using fillers, high processability and storage stability are achieved, and the transparency and hardness of the coating film are improved.
Patent Information
- Application Number
- CN202380053030.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-04-27
- Publication Date
- 2025-03-04
AI Technical Summary
In the absence of fillers, it is difficult to achieve excellent adhesion, appropriate contact time and appropriate viscosity to the substrate without using fillers, resulting in insufficient processability and storage stability, and the prepared coating film is poor in transparency and hardness.
The moisture-cured silicone composition containing organohydroxypolysiloxane, organopolysiloxane, alkoxy group-containing silane compounds, curing catalysts and tackifiers is used. By combining these components, the viscosity and curing time of the composition are adjusted to ensure excellent adhesion and transparency to the substrate.
Excellent adhesion to the substrate, appropriate contact time and appropriate viscosity are achieved, processability and storage stability are improved, and coating films with excellent transparency and hardness are prepared without filler.
Smart Images

Figure BDA0005236414050000091 
Figure BDA0005236414050000101 
Figure BDA0005236414050000131
Abstract
Description
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority based on Korean Patent Application No. 10-2022-0089773 filed on July 20, 2022, and all contents disclosed in the related Korean Patent Application are incorporated as part of this specification. Technical Field
[0003] The present disclosure relates to a moisture-curable silicone composition that exhibits adhesion to a substrate, an appropriate set-to-touch time, and an appropriate viscosity to be excellent in processability, exhibits excellent storage stability, exhibits excellent transparency and hardness in a prepared coating film, and exhibits less surface tackiness. Background Art
[0004] Since the organopolysiloxane composition is cured at a normal temperature of 25°C without additional heating to produce a cured product, contact moisture is generated in the air, so the organopolysiloxane composition may undergo a curing reaction and may be formed in a single-component type. Therefore, since the composition does not require a separate previous process, the composition shows excellent processability. Therefore, the single-component moisture-curing organopolysiloxane composition has been widely used as an elastic adhesive and coating agent in the field of electrical and electronic industries, as well as a building sealant. According to the type of by-products generated during the curing process, this single-component moisture-curing organopolysiloxane composition is divided into acetate type, oxime type, alcohol type and acetone type. Among them, the alcohol type organopolysiloxane composition is widely used due to its advantages of low odor and no corrosion to metal substrates, and is widely used in sensitive fields such as electrical and electronic fields.
[0005] Specifically, Japanese Patent No. 4045439 (Patent Document 1) discloses a room temperature curing organopolysiloxane composition comprising an organopolysiloxane, a branched organopolysiloxane, a silane compound containing a hydrolyzable group, and a silane coupling agent. However, conventional moisture curing organopolysiloxane compositions include fillers such as calcium carbonate to reduce the transparency of the cured material, thereby reducing the visibility of the mounted circuit (when coated on an electronic circuit board), which causes inconvenience during the process, making it impossible to detect a faulty component when a circuit board fails, thereby exhibiting poor adhesion to the substrate.
[0006] Therefore, there is a need for research on an excellent moisture-curable silicone composition that exhibits excellent adhesion to a substrate, an appropriate contact time and an appropriate viscosity to allow excellent workability, exhibits excellent storage stability, exhibits curability at normal temperature, and exhibits excellent transparency in a coating film prepared without containing a filler such as calcium carbonate. Summary of the invention
[0007]
Technical issues
[0008] Therefore, the present invention relates to an excellent curable silicone composition which has excellent adhesion to a substrate, has an appropriate contact time and an appropriate viscosity to make workability excellent, has excellent storage stability, shows curability at normal temperature, and shows excellent transparency in a coating film prepared without using a filler such as calcium carbonate.
[0009]
Technical solution
[0010] The present invention provides a moisture-curable siloxane composition, which comprises an organic hydroxy polysiloxane, an organic polysiloxane, an alkoxy-containing silane compound, a curing catalyst and a tackifier.
[0011] The organohydroxypolysiloxane comprises repeating units containing alkoxy groups,
[0012] The organopolysiloxane includes a first organopolysiloxane capped at opposite ends with an alkoxy group and a second organopolysiloxane capped at opposite ends with a silanol group, and
[0013] Adhesion promoters include cyclosiloxane based compounds.
[0014] Furthermore, the present invention provides a cured product prepared by curing the silicone composition.
[0015]
Beneficial Effects
[0016] According to the present disclosure, the moisture-curable siloxane composition shows excellent adhesion to the substrate, appropriate contact time and appropriate viscosity to make the processability excellent, and shows excellent storage stability, and shows curability at room temperature. In addition, since the siloxane composition does not contain fillers such as calcium carbonate, the prepared coating film shows excellent transparency and hardness, and shows low surface viscosity. Therefore, the siloxane composition is very suitable as a material in sensitive fields such as electrical or electronic fields, especially adhesives, coating agents, potting agents, and sealants. DETAILED DESCRIPTION
[0017] Hereinafter, the present disclosure will be described in detail.
[0018] In the present specification, “(meth)acrylic acid” means “acrylic acid” and / or “methacrylic acid”, and “(meth)acrylate” means “acrylate” and / or “methacrylate”.
[0019] In addition, the viscosity is measured by a method well known in the art. For example, the viscosity may be a value measured at 25°C using, for example, a Brookfield viscometer (LVDV) or a rheometer (MCR301; Anton Paar).
[0020] Moisture curing silicone composition
[0021] The present invention provides a moisture-curable siloxane composition, which comprises an organic hydroxy polysiloxane, an organic polysiloxane, an alkoxy-containing silane compound, a curing catalyst and a tackifier. Organic hydroxy polysiloxane
[0022] The organohydroxypolysiloxane improves the hardness of the cured product by forming the main skeleton of the siloxane composition.
[0023] The organohydroxy polysiloxane includes a repeating unit containing an alkoxy group. For example, the organohydroxy polysiloxane can be represented by Chemical Formula 1.
[0024] [Chemical formula 1]
[0025] [SiO 1 / 2 (R 1 )3] a [SiO 1 / 2 (OR 2 )3] b [SiO 2 / 2 (OR 3 )2] c [SiO 3 / 2 (OR 4 )] d [SiO 4 / 2 ] e (OH) In chemical formula 1,
[0026] R 1 -R 4 are each independently hydrogen, or a substituted or unsubstituted aralkyl, alkyl, cycloalkyl, alkenyl or aryl group,
[0027] 'a' is greater than 0.2 and less than 0.6,
[0028] 'b+c+d' is greater than 0.01 and less than 0.2,
[0029] 'e' is '0.09' to '0.7',
[0030] 'f' is greater than '0' and less than '0.05', and
[0031] 'a+b+c+d+e+f' equals 1.
[0032] For example, R 1 -R 4are each independently hydrogen, or substituted or unsubstituted C 7-15 Aralkyl, C 1-15 Alkyl, C 5-15 Cycloalkyl, C 2-10 Alkenyl, or C 6-15 In this case, the substituent may be substituted by a halogen atom or a cyanoalkyl group. Specifically, R 1 -R 4 Each can be independently hydrogen; alkyl such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl or dodecyl; cycloalkyl such as cyclohexyl; alkenyl such as vinyl and allyl; aryl such as phenyl, tolyl and xylyl; aralkyl such as benzyl, 2-phenylethyl or 2-phenylpropyl, more specifically, can be hydrogen or methyl. In this case, alkyl and alkenyl can be linear or branched.
[0033] Specifically, 'a' may range from 0.3-0.55 or 0.38-0.50, 'b+c+d' may range from 0.02-0.18 or 0.05-0.15, 'e' may range from 0.2-0.6 or 0.35-0.55, 'f' may be greater than 0 and less than 0.04, or greater than 0 and less than 0.02, and 'a+b+c+d+e+f' may be 1.
[0034] When 'a' is less than the above range, the mechanical properties of the cured product may be reduced, causing the cured product to lose its function as a coating agent. When 'a' exceeds the above range, a higher hardness of the cured product may not be achieved. In addition, when 'b+c+d' is less than the above range, curing may fail, or a cured product with a higher hardness may not be obtained. When 'b+c+d' exceeds the above range, the curing rate may be excessively reduced, or a cured product with higher brittleness may be formed, thereby limiting industrial use. In addition, when 'e' is less than the above range, the Q unit ([SiO 4 / 2 ] repeating unit) is reduced, so the hardness of the cured product may not be achieved. When 'e' exceeds the above range, the brittleness of the cured product increases, resulting in limited industrial use. In addition, when 'f' is greater than the above range, the coating surface of the cured product may be more sticky, causing inconvenience in the process and in the working environment, such as dust sticking.
[0035] The hydroxyl content of the organohydroxypolysiloxane may range from greater than 0 to 0.24 mmol / g, or greater than 0 to 0.15 mmol / g. When the hydroxyl content of the organohydroxypolysiloxane exceeds the above range, the stickiness of the coating surface of the cured product may increase, causing inconvenience in the process and in the working environment, such as dust adhesion.
[0036] In addition, the organohydroxy polysiloxane can be prepared by preparing a polysiloxane having at least one hydroxydimethylsiloxy group (-Si(CH3)2OH), at least one trimethylsiloxy group (-Si(CH3)3) and at least one Q functional group (-SiO 4 / 2 ) is prepared by reacting the branched organopolysiloxane with a tetrafunctional alkoxysilane. The method for preparing the branched organopolysiloxane may be well known to those skilled in the art. For example, the method disclosed in U.S. Pat. No. 2,676,182 and U.S. Pat. No. 2,814,601 can be used for the method for preparing the branched organopolysiloxane. When the organohydroxypolysiloxane can be prepared by reacting the branched organopolysiloxane with a tetrafunctional alkoxysilane, after the branched organopolysiloxane is prepared as described above, it is preferred that the content of each repeating unit can be easily adjusted to maintain the target amount, but the present disclosure is not limited thereto.
[0037] Organopolysiloxane
[0038] The organopolysiloxane is used to adjust the viscosity of the silicone composition and to impart flexibility to the prepared cured product.
[0039] The organopolysiloxane includes a first organopolysiloxane end-capped with an alkoxy group at opposite ends and a second organopolysiloxane end-capped with a silanol group at opposite ends. When the siloxane composition includes two organopolysiloxanes having different end-capping groups as described above, that is, when the first organopolysiloxane and the second organopolysiloxane are used together, the siloxane composition can be rapidly cured even at normal temperature even in the absence of moisture because the silicon-bonded hydroxyl group and the silicon-bonded alkoxy group are cured by a condensation catalyst.
[0040] Meanwhile, when only the first organopolysiloxane terminated by alkoxy groups at opposite ends is used as the organopolysiloxane, the prepared coating film may crack under high reliability evaluation conditions. In addition, when only the second organopolysiloxane terminated by silanol groups at opposite ends is used, the hardness of the prepared coating film is insufficient. Therefore, the protective performance of materials in the electrical and electronic fields such as PCBs is insufficient.
[0041] <First Organopolysiloxane>
[0042] The first organopolysiloxane may be represented by, for example, Formula 2 below.
[0043] [Chemical formula 2]
[0044] [(R 5 O) (3-i) Si(R 6 ) i ]-Y 1 -[SiO 2 / 2(R 7 )2] j -[Si(R 8 )2]-Y 2 -[(R 5 O) (3-i) Si(R 6 ) i ]
[0045] In chemical formula 2,
[0046] R 5 -R 8 are each independently a substituted or unsubstituted aralkyl, alkyl, cycloalkyl, alkenyl or aryl group,
[0047] Y 1 and Y 2 are each independently an oxy group or a substituted or unsubstituted alkylene group,
[0048] 'i' is 0 or 1, and
[0049] 'j' is an integer from 1 to 300.
[0050] For example, R 5 -R 8 Each independently is a saturated or unsaturated C 7-15 Aralkyl, C 1-15 Alkyl, C 5-15 Cycloalkyl, C 2-10 Alkenyl or C 6-15 In this case, the substituent may be substituted by a halogen atom or a cyanoalkyl group. Specifically, R 5 -R 8 Each may independently be an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl or dodecyl; a cycloalkyl group such as cyclohexyl; an aralkyl group such as vinyl and allyl; an aryl group such as phenyl, tolyl or xylyl, an aralkyl group such as benzyl, 2-phenylethyl or 2-phenylpropyl, and more specifically, may be methyl.
[0051] Y 1 and Y 2 Each may independently be an oxy group; or a substituted or unsubstituted C 1-15 Specifically, Y 1 and Y 2 Each can be independently C 1-10 Alkylene or C 1-7Alkylene, alkylene can be linear or branched. In this case, alkylene refers to a branched, linear or cyclic divalent group derived by removing a hydrogen atom from a carbon atom of an alkyl group. For example, alkylene can include methylene (-CH2-), 1,1-ethylene (-CH(CH3)-), 1,2-ethylene (-CH2CH2-), 1,1-propylene (-CH(CH2CH3)-), 1,2-propylene (-CH2CH(CH3)-), 1,3-propylene (-CH2CH2CH2-), 1,4-butylene (-CH2CH2CH2CH2-) or 2,4-butylene (-CH2(CH3)CH2CH2-), but the present disclosure is not limited thereto.
[0052] In this case, the alkyl and alkenyl groups may be linear or branched.
[0053] The viscosity of the first organopolysiloxane at 25° C. ranges from 10 to 10,000 cP, or from 40 to 6,000 cP. When the viscosity of the first organopolysiloxane at 25° C. is below the above range, strong volatility may cause work risks, or the mechanical properties of the cured product may be weakened. When the viscosity exceeds this range, the viscosity of the siloxane composition may increase, and thus the use of the siloxane composition may be limited.
[0054] Specifically, the first organopolysiloxane may include at least two first organopolysiloxanes having different viscosities at 25° C. When at least two first organopolysiloxanes having different viscosities are used as described above, the viscosity of the composition can be kept low and the prepared coating film can be flexible to prevent easy breakage.
[0055] For example, the first organopolysiloxane may include a (1-1) organopolysiloxane having a viscosity range of 10cP-500cP or 40cP-100cP and a (1-2) organopolysiloxane having a viscosity range of 1000cP-10000cP or 4000cP-6000cP. When the viscosity of the (1-1) organopolysiloxane is less than the range, it exhibits strong volatility, resulting in insufficient processability of the composition. When the viscosity of the (1-1) organopolysiloxane exceeds the range, the siloxane composition containing it exhibits a higher viscosity, and thus the working method may be limited. When the viscosity of the (1-2) organopolysiloxane is less than the range, the prepared coating film is fragile and easily cracked. When the viscosity of the (1-2) organopolysiloxane exceeds the range, the composition exhibits a higher viscosity, and thus the working method may be limited.
[0056] The first organopolysiloxane may be included in the siloxane composition in an amount of 55-140 parts by weight or 60-110 parts by weight based on 100 parts by weight of the organohydroxypolysiloxane. When the content of the first organopolysiloxane is less than the content range, the siloxane composition exhibits excessively high viscosity, and thus spraying and other work may fail. When the content of the first organopolysiloxane exceeds the content range, the content of the organohydroxypolysiloxane becomes low, and thus the hardness or strength of the prepared cured product may be insufficient.
[0057] Specifically, based on 100 parts by weight of the organic hydroxy polysiloxane, the (1-1)th organic polysiloxane may be included in an amount ranging from 1 to 100 parts by weight, 4 to 80 parts by weight, or 30 to 60 parts by weight, and the (1-2)th organic polysiloxane may be included in an amount ranging from 20 to 100 parts by weight, 20 to 70 parts by weight, or 25 to 50 parts by weight. When the amount of the (1-1)th organic polysiloxane is less than the range, the siloxane composition exhibits a higher viscosity, and thus the work may fail. When the amount of the (1-1)th organic polysiloxane exceeds the range, the strength of the cured product may be insufficient. When the amount of the (1-2)th organic polysiloxane is less than the range, the surface of the cured product may be defective. When the amount of the (1-2)th organic polysiloxane exceeds the range, the strength of the cured product may be insufficient.
[0058] <Second Organopolysiloxane>
[0059] The second organopolysiloxane may be represented by, for example, Formula 3 below.
[0060] [Chemical formula 3]
[0061] HO-[SiO 2 / 2 (R 10 )2] k -OH
[0062] In chemical formula 3,
[0063] R 10 It may be a substituted or unsubstituted aralkyl group, alkyl group, cycloalkyl group, alkenyl group or aryl group.
[0064] "k" is a number that allows the viscosity of the second organopolysiloxane at 25°C to be 100 to 100,000 cP.
[0065] For example, R 10 independently saturated or unsaturated C 7-15 Aralkyl, C 1-15 Alkyl, C 5-15 Cycloalkyl, C 2-10 Alkenyl or C 6-15 In this case, the substituent may be substituted by a halogen atom or a cyanoalkyl group. Specifically, R10 It may independently be an alkyl group such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl or dodecyl; a cycloalkyl group such as cyclohexyl; an alkenyl group such as vinyl and allyl; an aryl group such as phenyl, tolyl or xylyl; an aralkyl group such as benzyl, 2-phenylethyl or 2-phenylpropyl, and more specifically, may be methyl.
[0066] In this case, the alkyl and alkenyl groups may be linear or branched.
[0067] The viscosity of the second organopolysiloxane at 25° C. ranges from 100 to 100,000 cP, or from 500 to 10,000 cP, or from 800 to 6,000 cP. When the viscosity of the second organopolysiloxane at 25° C. is less than this range, the curing rate of the siloxane composition is too high, and thus workability may be reduced. When the viscosity of the second organopolysiloxane exceeds this range, the curing rate of the siloxane composition is too low, and thus productivity may be reduced, or foreign substances may penetrate into the cured product during curing.
[0068] The second organopolysiloxane may be included in the siloxane composition in an amount of 30-100 parts by weight, 35-95 parts by weight, or 50-70 parts by weight based on 100 parts by weight of the organohydroxypolysiloxane. When the content of the second organopolysiloxane is less than the content range, the adhesive force during the curing process may be weakened. When the content of the second organopolysiloxane exceeds the content range, the viscosity of the coating surface of the cured product may increase, and thus the possibility of the surface of the cured product being contaminated during curing at room temperature increases, thereby causing inconvenience in use.
[0069] The organohydroxypolysiloxane, the first organopolysiloxane, and the second organopolysiloxane may be included in the composition in a weight ratio of 1:0.55-1.4:0.3-1.0, or 1:0.6-1.1:0.5-0.7.
[0070] When the weight ratio of the first organopolysiloxane is less than the above range based on the content of the organohydroxypolysiloxane, the flexibility of the cured product after curing is reduced, so the brittleness is significantly weakened and the curing rate is significantly reduced. When the weight ratio of the first organopolysiloxane is greater than the above range, the content of the organohydroxypolysiloxane having a branched structure is reduced, so the hardness of the cured product cannot reach the target hardness.
[0071] When the weight ratio of the second organopolysiloxane based on the content of the organohydroxypolysiloxane is less than the above range, the adhesive force of the cured product may be reduced. When the weight ratio of the second organopolysiloxane exceeds the range, the surface of the cured product may be sticky.
[0072] Alkoxy-containing silane compounds
[0073] The alkoxy-containing silane compound controls the contact time of the silicone composition and adjusts the viscosity of the silicone composition.
[0074] In addition, the silane compound containing alkoxy can include 1-10 silicon atoms in one molecule.For example, the silane containing alkoxy can include at least one selected from the group consisting of dimethyldimethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, vinylmethyldimethoxysilane, dimethyldiethoxysilane and methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, vinyltriethoxysilane, phenyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane and tetraisopropoxysilane.Specifically, the silane compound containing alkoxy can be a trialkoxy-containing silane such as methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, vinyltriethoxysilane, phenyltriethoxysilane, tetramethoxysilane or tetraethoxysilane.
[0075] The alkoxy-containing silane compound may be included in the siloxane composition in an amount of 10-85 parts by weight, 15-70 parts by weight, or 20-50 parts by weight based on 100 parts by weight of the organohydroxy polysiloxane. When the content of the alkoxy-containing silane is less than this range, the tack-free time of the composition may be excessively shortened, and the viscosity of the composition may increase, thereby reducing processability. When the content of the alkoxy-containing silane exceeds this range, as the tack-free time of the composition increases, the curing time may be extended, thereby reducing productivity or reducing the strength of the cured product.
[0076] In addition, the siloxane composition may include an alkoxy-containing silane compound and a curing catalyst in a weight ratio of 3:1 to 40:1, a weight ratio of 3:1 to 25:1, or a weight ratio of 3:1 to 15:1. When the weight ratio between the alkoxy-containing silane compound and the curing catalyst is less than the range, that is, when a small amount of the alkoxy-containing silane compound is included based on the weight of the curing catalyst, the hardness of the cured product may be reduced and the cured product may be discolored. In addition, when the weight ratio between the alkoxy-containing silane compound and the curing catalyst exceeds the range, that is, when an excessive amount of the alkoxy-containing silane compound is included based on the weight of the curing catalyst, the curing rate of the cured product is excessively reduced, and thus the processability may be insufficient or the cured product may not be cured.
[0077] Curing catalyst
[0078] The curing catalyst accelerates the curing of the composition.
[0079] The curing catalyst is not particularly limited as long as the curing catalyst can be used for moisture-curing silicone compositions. For example, the curing catalyst can be an organic tin compound such as dibutyl dimethoxytin, dibutyl tin diacetate, dibutyl tin dioctoate, dibutyl tin dilaurate, dibutyl tin bis(acetylacetonate), dibutyl tin bis(benzyl maleate), dimethyl dimethoxytin, dimethyl tin diacetate, dioctyl tin dioctoate, dioctyl tin dilaurate, tin dioctoate, or tin dilaurate; an organic titanium compound such as tetraisopropyl titanate, tetra-n-butyl titanate, tetra-tert-butyl titanate, tetra-n-propyl titanate, tetra-2-ethylhexyl titanate, diisopropyl di-tert-butyl titanate, dimethoxybis-acetylacetonato titanium, diisopropoxybis-ethyl acetoacetate titanium, di-tert-butoxybis-ethyl acetoacetate titanium, or di-tert-butoxybis-methyl acetoacetate titanium; and an amine compound such as 3-aminopropyl trimethoxysilane or tetramethylguanidopropyl trimethoxysilane.
[0080] In addition, based on 100 parts by weight of the organohydroxy polysiloxane, the curing catalyst may be included in the composition in an amount of 1-10 parts by weight, 1-9 parts by weight, or 4-9 parts by weight. When the content of the curing catalyst is less than the content range, the curing rate of the composition may be reduced, or the curing may fail. When the content of the curing catalyst exceeds the content range, during the storage of the siloxane composition, the viscosity may increase, or in severe cases the siloxane composition may solidify, and thus the use of the siloxane composition may be difficult.
[0081] Tackifier
[0082] Adhesion promoters can impart adhesion to substrates.
[0083] The tackifier may include a cyclosiloxane-based compound. When the tackifier includes a cyclosiloxane-based compound, the tackifier may react with the coated substrate to exert adhesion. For example, since the tackifier includes a cyclosiloxane group, the substrate and the cyclosiloxane group react with each other to increase adhesion.
[0084] In addition, the tackifier may be, for example, cyclotrisiloxane (trimer), cyclotetrasiloxane (tetramer), or cyclopentasiloxane (pentamer). Specifically, the tackifier may be a compound represented by the following Chemical Formula 4.
[0085] [Chemical formula 4]
[0086]
[0087] In chemical formula 4,
[0088] R 20 -R 22 , R 25 and R 26Each is independently a substituted or unsubstituted alkyl group.
[0089] R 23 and R 24 Each is independently a substituted or unsubstituted alkylene group.
[0090] 'm', 'n' and 'x' can each independently be 1-3.
[0091] For example, R 20 -R 22 Each can be independently C 1-5 Alkyl or C 1-3 Alkyl, R 23 and R 24 Each can be independently C 1-15 Alkylene, C 1-10 Alkylene or C 1-5 Alkylene, R 25 and R 26 Each can be independently C 1-5 Alkyl or C 1-3 alkyl.
[0092] For example, 'm+n' may be 2-6 or 3-4, 'm' may be 1-4 or 1-3, and 'n' may be 1-4 or 1-2.
[0093] In this case, the alkylene group refers to a branched, linear or cyclic divalent group derived by removing one hydrogen atom from a carbon atom of an alkyl group. For example, the alkylene group may include a methylene group (-CH2-), a 1,1-ethylene group (-CH(CH3)-), a 1,2-ethylene group (-CH2CH2-), a 1,1-propylene group (-CH(CH2CH3)-), a 1,2-propylene group (-CH2CH(CH3)-), a 1,3-propylene group (-CH2CH2CH2-), a 1,4-butylene group (-CH2CH2CH2CH2-) or a 2,4-butylene group (-CH2(CH3)CH2CH2-), but the present disclosure is not limited thereto.
[0094] The alkenyl and alkyl groups may be linear or branched.
[0095] For example, the tackifier may include an ester group and an alkoxy group. Specifically, the tackifier may include an ester group and an alkoxy group having 1 to 5 carbon atoms or 1 to 3 carbon atoms. When the tackifier includes an ester group and an alkoxy group, the ester group of the tackifier reacts with the polar group of the substrate, and the alkoxy group of the tackifier reacts with the alkoxy group or hydroxyl group of the organohydroxypolysiloxane or organopolysiloxane, thereby significantly improving the adhesion of the prepared cured product.
[0096] The adhesion promoter may contain, for example, dimethylsiloxy units ((CH3)2SiO 2 / 2) and methylhydrogensiloxy units (CH3(H)SiO 2 / 2 Specifically, the adhesion promoter may include, for example, dimethylsiloxy units ((CH3)2SiO 2 / 2 ), methylhydrogensiloxane unit (CH3(H)SiO 2 / 2 More specifically, the tackifier may be a compound represented by Chemical Formula 5.
[0097] [Chemical formula 5]
[0098]
[0099] Specifically, the adhesion promoter may include 3-(trimethoxysilyl)propyl α,2,4,6,6,8-hexamethylcyclotetrasiloxane propionate.
[0100] Additionally, the tackifier may include acrylic compounds.
[0101] Specifically, the tackifier may include a first tackifier including a cyclosiloxy group and a second tackifier including an acryl group. When the siloxane composition includes the first tackifier and the second tackifier as tackifiers, the cyclosiloxy group and the acryl group, which are heterogeneous functional groups, react with each other to enhance adhesion.
[0102] Since the second tackifier includes an acryl group, the substrate and the acryl group react with each other to exert adhesion.
[0103] In addition, the second adhesion promoter may include a silane compound containing a (meth) acrylic group. Specifically, the second adhesion promoter may include at least one selected from the group consisting of 3-(methacryloxypropyl)trimethoxysilane, 3-(methacryloxypropyl)triethoxysilane, 3-(acryloxypropyl)trimethoxysilane and 3-(acryloxypropyl)triethoxysilane.
[0104] The first tackifier and the second tackifier may be included in a weight ratio of 1:0.3 to 1:40, or 1:1 to 1:10. When the weight ratio between the first tackifier and the second tackifier is less than the range, the adhesive force of the cured product is poor. When the weight ratio between the first tackifier and the second tackifier exceeds the range, the surface of the cured product may be defective.
[0105] The tackifier may be included in the composition in an amount of 0.05-10 parts by weight, 0.5-7 parts by weight, or 1-4 parts by weight based on 100 parts by weight of the organohydroxypolysiloxane. When the content of the tackifier is less than the content range, the adhesive force of the composition may be insufficient. When the content of the tackifier exceeds the content range, the tackifier may not be used as a clear coating agent due to the turbid appearance of the cured product.
[0106] Specifically, based on 100 parts by weight of the organohydroxy polysiloxane, the siloxane composition may include 0.05-5 parts by weight or 0.1-4 parts by weight of the first tackifier and 0-9 parts by weight or 0.2-7 parts by weight of the second tackifier. When the content of the first tackifier is less than this range, the surface of the cured product may be delaminated from the substrate. When the content of the first tackifier exceeds this range, the appearance may be discolored after curing.
[0107] additive
[0108] The moisture-curable silicone composition may further contain additives commonly used in the art, such as antistatic agents, pigments, colorants, ultraviolet absorbers, fluorescent agents, heat-resistant agents, flame retardants, antioxidants, free radical scavengers or light stabilizers.
[0109] The moisture-curable silicone composition may have a viscosity of up to 1500 cP at 25° C., a viscosity range of 50-1500 cP or 100-1000 cP. In addition, the moisture-curable silicone composition may exhibit a contact time of up to 15 minutes, a range of 1 minute to 10 minutes, or a range of 3 minutes to 10 minutes based on JIS K6249.
[0110] In addition, since the moisture-curable siloxane composition does not contain fillers, the moisture-curable siloxane composition shows excellent transparency and hardness in the prepared cured product. Therefore, the moisture-curable siloxane composition is suitable for sensitive fields such as electrical and electronic fields. In this case, the filler can be silicon dioxide.
[0111] As described above, according to the present disclosure, the moisture-curable silicone composition has excellent adhesion to a substrate, an appropriate contact time, and an appropriate viscosity to show excellent curability and processability at normal temperature.
[0112] Cured product
[0113] According to the present disclosure, a cured product is prepared by curing a silicone composition.
[0114] The Shore A hardness of the cured product having an average thickness of 6 mm is in the range of 80-95, or 85-94.
[0115] The shear strength of the cured product having an average thickness of 2 mm is at least 2.5 MPa, at least 3.5 MPa, or 3.5 MPa to 5.0 MPa.
[0116] As described above, the cured product exhibits excellent transparency and excellent hardness, exhibits less surface tackiness, and exhibits excellent thermal shock resistance, and thus the cured product is suitable for use in sensitive fields such as electrical and electronic fields.
[0117] [Implementation Methods of the Invention]
[0118] Hereinafter, the present disclosure will be described in detail by way of examples. However, these examples are only for illustrative purposes, and the scope of the present disclosure is not limited to these examples even in any sense.
[0119] Preparation Example 1. Preparation of organohydroxypolysiloxane
[0120] 1-1: Preparation of organic hydroxy polysiloxane-1 (Synthesis Example 1)
[0121] A trimethylsiloxy-terminated branched organopolysiloxane (weight average molecular weight (MW): 3000 g / mol, silanol content: 2.05 wt %, manufacturer: KCC silicon) and xylene were mixed in a flask in a weight ratio of 1:1, and a mixture was prepared. Afterwards, 22 parts by weight of tetramethoxysilane were added to 100 parts by weight of the mixture and stirred for 10 minutes. 0.5 parts by weight of sulfuric acid used as a catalyst was introduced into the result and stirred at 25°C for 24 hours, and 10 parts by weight of NaHCO3 were introduced into the result and stirred for 1 hour. Afterwards, a filter was used to filter to remove NaHCO3, thereby obtaining a transparent liquid (organohydroxypolysiloxane-1) having a viscosity of 8 cP and a solid content of 60 wt % at 25°C. Afterwards, the pressure was reduced to 5 torr at 60°C to remove xylene.
[0122] As 29 Si NMR analysis results show that the prepared organohydroxypolysiloxane-1 consists of 43.89 mol% SiO 1 / 2 (CH3)3 units, 2.60 mol% SiO 1 / 2 (OCH3)3 units, 2.91 mol% SiO 2 / 2 (OCH3)2 units, 3.82 mol% SiO 3 / 2 (OCH3) units, 0.08 mol% SiO 3 / 2 (OH) units and 46.70 mol% SiO 4 / 2 Unit composition: In addition, the prepared organohydroxypolysiloxane-1 had 0.011 mmol / g of OH groups and 2.35 mmol / g of OCH3 groups.
[0123] 1-2: Preparation of organic hydroxy polysiloxane-2 (Synthesis Example 2)
[0124] A trimethylsiloxy-terminated branched organopolysiloxane (weight average molecular weight (MW): 3000 g / mol, silanol content: 2.05 wt %, manufacturer: KCC silicon) and xylene were mixed in a flask in a weight ratio of 1:1, and a mixture was prepared. Afterwards, 33 parts by weight of tetramethoxysilane were added to 100 parts by weight of the mixture and stirred for 10 minutes. 0.5 parts by weight of sulfuric acid used as a catalyst was introduced into the result and stirred at 25°C for 24 hours, and 10 parts by weight of NaHCO3 were introduced into the result and stirred for 1 hour. Afterwards, a filter was used to filter to remove NaHCO3, thereby obtaining a transparent liquid (organohydroxypolysiloxane-1) having a viscosity of 8 cP and a solid content of 60 wt % at 25°C. Afterwards, the pressure was reduced to 5 torr at 60°C to remove xylene.
[0125] As 29 Si NMR analysis results show that the prepared organohydroxypolysiloxane-2 consists of 43.52 mol% SiO 1 / 2 (CH3)3 units, 2.78 mol% SiO 1 / 2 (OCH3)3 units, 3.77 mol% SiO 2 / 2 (OCH3)2 units, 4.04 mol% SiO 3 / 2 (OCH3) units, 0.1 mol% SiO 3 / 2 (OH) units and 45.79 mol% SiO 4 / 2 Unit composition. In addition, the prepared organohydroxypolysiloxane-2 had 0.11 mmol / g OH group and 2.66 mmol / g OCH3 group.
[0126] 1-3: Preparation of organic hydroxy polysiloxane-3
[0127] As organic hydroxy polysiloxane-3 29 Si NMR analysis results show that the SiO 1 / 2 (CH3)3 units, 4.38 mol% SiO 3 / 2 (OH) units and 50.3 mol% SiO 4 / 2 In addition, the organohydroxypolysiloxane-3 has 0.11 mmol / g OH group and 0 mmol / g OCH3 group.
[0128] Experimental Example 1-22. Preparation of moisture-curable siloxane composition
[0129] The moisture curing silicone compositions were prepared by mixing the components described in Tables 1-3.
[0130] Table 1
[0131]
[0132] Table 2
[0133]
[0134] Table 3
[0135]
[0136] The manufacturer, product name or material name of each component used in the experimental examples is shown in Table 4, and the viscosity of the organopolysiloxane at 25° C. is a value measured by a Brookfield viscometer (LVDV).
[0137] Table 4
[0138]
[0139]
[0140] Test case: Feature evaluation
[0141] The physical properties of the moisture-curable silicone composition of the experimental example and the cured sheet prepared therefrom were measured in the following manner. The results are shown in Table 5.
[0142] Specifically, a cured sheet was prepared by curing the moisture-curable silicone composition according to the Experimental Example at a temperature of 25° C. and a relative humidity of 50% for seven days in a mold for molding a sheet having a thickness of 2 mm.
[0143] (1) Viscosity
[0144] The viscosity of the moisture-curable silicone composition according to the Experimental Example was measured using a rheometer (MCR301; Anton Paar) at 25° C. at a shear force of 10 / s.
[0145] (2) Contact time
[0146] The contact time of the moisture-curable silicone composition was measured based on JIS K 6249. Specifically, after the composition was coated on a PET film to a thickness of 60 μm, the surface was lightly touched with a finger, and the time during which the composition was not transferred to the tip of the finger was measured.
[0147] (3) Hardness
[0148] After three cured sheets were laminated to a thickness of 6 mm, the results were measured using a Shore A durometer at 25°C.
[0149] (4) Shear strength
[0150] The moisture-curable silicone composition was applied to the end of an aluminum specimen having a width of 2.5 cm and a length of 6 cm in a width of 2.5 cm and a length of 0.5 cm, and another aluminum specimen was placed thereon to give a thickness of 2 mm. Then, it was cured at a temperature of 25° C. and a relative humidity of 50% for 7 days, and then its shear strength was measured using a universal testing machine (UTM FID) to determine the adhesive force.
[0151] (5) Surface viscosity
[0152] When a finger lightly touches and lifts off the surface of the cured sheet, the degree of tackiness is evaluated. In this case, a relative evaluation is performed by setting significantly lower tack to "1" and significantly higher tack to "5".
[0153] (6) Thermal shock test
[0154] The moisture-curable silicone composition was coated on a PCB substrate and cured for seven days at a temperature of 25°C and a relative humidity of 50%. After that, assuming that it was placed at -40°C for 30 minutes, it was placed at 125°C for 30 minutes by a thermal shock tester as one cycle, and a total of 1,000 cycles were performed. After that, after being stored at 25°C for 1 day, the delamination and cracking of the coating (including the cured product of the moisture-curable silicone composition) were measured by microscope. In this case, the delaminated or cracked coating was marked as "O", and the non-delaminated or cracked coating was marked as "X".
[0155] (7) High temperature and high humidity test
[0156] The moisture-curable silicone composition was coated on a PCB substrate and cured for seven days at a temperature of 25°C and a relative humidity of 50%. After being placed at a temperature of 85°C and a relative humidity of 85% for 1000 hours by a high temperature and high humidity tester, the result was stored at 25°C for one day. After that, the delamination and cracking of the coating (including the cured product of the moisture-curable silicone composition) were measured by microscopy. In this case, the delamination and / or cracked coating was marked as "O", and the non-delamination or cracked coating was marked as "X".
[0157] (8) Storage stability
[0158] The moisture-curable organopolysiloxane composition was placed in a glass vial, sealed, and stored in an oven at 80° C. for 14 days, and then the contact time was measured in the same manner as in item (2).
[0159] Table 5
[0160]
[0161]
[0162] As shown in Table 5, the viscosity and contact time of the moisture-curable silicone composition according to Experimental Examples 1 to 10 are appropriate, showing excellent processability and excellent storage stability. In addition, the cured sheet prepared using the composition is excellent in appearance, hardness and shear strength, which shows excellent mechanical properties, and is excellent in heat resistance, which shows excellent thermal shock test and excellent high temperature and high humidity test, and shows low surface tack.
[0163] Meanwhile, the cured sheets prepared by Experimental Examples 11, 16, 17 and 20, which only included the third tackifier containing an epoxy group, showed insufficient shear strength. In particular, the sheet containing the organohydroxypolysiloxane-3 containing no alkoxy group from Experimental Example 11 had significantly severe surface tackiness. In addition, the sheet containing an excessive amount of the third tackifier of Experimental Example 16 had an opaque appearance, insufficient hardness, surface tackiness, and insufficient heat resistance. In addition, the sheet containing a smaller amount of the third tackifier of Experimental Example 17 cracked due to insufficient heat resistance after being subjected to a thermal shock test.
[0164] In addition, Experimental Example 12, which contained 3-glycidyloxypropyltrimethoxysilane (third adhesion promoter) and 3-aminopropyltriethoxysilane (fourth adhesion promoter) as adhesion promoters and contained a small amount of curing catalyst, and Experimental Example 14, which contained a small amount of the second organic polysiloxane and an excess of an alkoxy-containing silane compound, failed to cure at room temperature and was not cured.
[0165] The sheet of Experimental Example 13 containing an excessive amount of curing catalyst was discolored.
[0166] In addition, the composition containing a small amount of the alkoxy-containing silane compound according to Experimental Example 15 had higher viscosity and longer contact time, showing insufficient processability and insufficient storage stability. Therefore, the sheet prepared therefrom showed insufficient hardness and surface stickiness.
[0167] The composition including an excessive amount of the second organopolysiloxane according to Experimental Example 18 showed insufficient storage stability, and thus a sheet prepared therefor showed insufficient hardness.
[0168] In addition, for Experimental Example 19 containing a relatively small amount of the second organopolysiloxane, the sheet showed insufficient heat resistance. Therefore, after the heat shock test and the high temperature and high humidity test, the sheet cracked.
[0169] Experimental Example 21 including a smaller amount of the first organopolysiloxane and Experimental Example 22 not including the second organopolysiloxane showed excessively high viscosity at 25°C. Therefore, processability was significantly insufficient, and the heat resistance of the sheet was insufficient, so the sheet cracked after the thermal shock test. In particular, the composition according to Experimental Example 21 showed insufficient storage stability, and even the surface of the sheet was sticky. In addition, Experimental Example 22 showed that the shear strength of the sheet was insufficient.
Claims
1. A moisture-curable siloxane composition comprising: Organic hydroxy polysiloxane, organic polysiloxane, alkoxy group-containing silane compound, curing catalyst and adhesion promoter, in, The organohydroxypolysiloxane comprises repeating units containing alkoxy groups, wherein the organopolysiloxane comprises a first organopolysiloxane capped at opposite ends with alkoxy groups and a second organopolysiloxane capped at opposite ends with silanol groups, and Among them, the adhesion promoter includes cyclosiloxane-based compounds.
2. The moisture-curable siloxane composition according to claim 1, wherein the organohydroxy polysiloxane is represented by the following chemical formula 1: [Chemical formula 1] [SiO 1 / 2 (R 1 )3] a [SiO 1 / 2 (OR 2 )3] b [SiO 2 / 2 (OR 3 )2] c [SiO 3 / 2 (OR 4 )] d [SiO 4 / 2 ] e (OH) f , in, In Chemical Formula 1, R 1 -R 4 are each independently hydrogen, or a substituted or unsubstituted aralkyl, alkyl, cycloalkyl, alkenyl or aryl group, 'a' is greater than "0.2" and less than "0.6", 'b+c+d' is greater than '0.01' and less than '0.2', 'e' is '0.09' to '0.7', 'f' is greater than '0' and less than '0.05', and 'a+b+c+d+e+f' is 1.
3. The moisture-curable siloxane composition according to claim 1, wherein the first organopolysiloxane is represented by the following Chemical Formula 2, and in, The first organopolysiloxane includes a (1-1) organopolysiloxane having a viscosity of 10 to 500 cP at 25° C.; and a (1-2) organopolysiloxane having a viscosity of 1000 to 10000 cP at 25° C., [Chemical formula 2] [(R 5 O) (3-i) Si(R 6 ) i ]-Y 1 -[SiO 2 / 2( R 7 )2] j -[Si(R 8 )2]-Y 2 -[(R 5 O) (3-i) Si(R 6 ) i ] Wherein, in Chemical Formula 2, R 5 -R 8 are each independently a substituted or unsubstituted aralkyl, alkyl, cycloalkyl, alkenyl or aryl group, Y 1 and Y 2 are each independently an oxy group or a substituted or unsubstituted alkylene group, 'i' is 0 or 1, and 'j' is an integer from 1 to 300.
4. The moisture-curable siloxane composition according to claim 1, wherein the second organopolysiloxane is represented by the following Chemical Formula 3: [Chemical formula 3] HO–[(SiO 2 / 2 (R 10 )2] k -OH in, In chemical formula 3, R 10 may be substituted or unsubstituted aralkyl, alkyl, cycloalkyl, alkenyl or aryl, and 'k' is a number that allows the viscosity of the second organopolysiloxane to be 100-100000 cP at 25°C.
5. The moisture-curable silicone composition according to claim 1, wherein the adhesion promoter is represented by the following chemical formula 4 [Chemical formula 4] in, In chemical formula 4, R 20 -R 22 and R 25 and R 26 are each independently a substituted or unsubstituted alkyl group, R 23 and R 24 are each independently a substituted or unsubstituted alkylene group, 'm', 'n' and 'x' may each independently be 1-3.
6. The moisture-curable silicone composition of claim 5, wherein the adhesion promoter comprises: a first adhesion promoter containing a cyclosiloxy group; and a second tackifier containing an acryl group, and The weight ratio of the first tackifier to the second tackifier is 1:0.3 to 1:
40.
7. The moisture-curable silicone composition according to claim 1, wherein 100 parts by weight of an organohydroxypolysiloxane, 55-140 parts by weight of a first organopolysiloxane, 30-100 parts by weight of a second organopolysiloxane, 10-85 parts by weight of an alkoxy-containing silane compound, 1-10 parts by weight of a curing catalyst, and 0.05-10 parts by weight of a tackifier are provided.
8. A cured product prepared by curing the silicone composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Apparatus for generating bubbles using drone
KR1020220089773A
Copolymeric siloxanes and methods of preparing them
US2676182A
Organopolysiloxane adhesive and pressure-sensitive adhesive tape containing same
US2814601A